2015
DOI: 10.1002/asjc.1081
|View full text |Cite
|
Sign up to set email alerts
|

Leader‐Following Output Synchronization for a Class of Uncertain Nonlinear Multi‐Agent Systems Under Uniformly Connected Network

Abstract: In this paper we study the cooperative global output regulation problem of a class of uncertain nonlinear multi-agent systems under dynamic network topology. Distributed dynamic observers are introduced to estimate the states of the leader system or the called exosystem. Furthermore, we propose a multi-channel input version of the changing supply rate theorem, through which the changing supply rate technique can be applied to the subsystem with multiple channels of the control inputs, and therefore control law… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Because of cooperative control widespread potential applications in various fields such as synchronized rise of guide way climbing frame (GWCF), formation control of mobile robots, distributed coordination of multiple dynamic systems (also known as multi-agent systems [1][2][3][4][5][6]), has achieved rapid development in recent decades. Consensus is one of the most popular topics in this area, which has received significant attention from numerous researchers [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Because of cooperative control widespread potential applications in various fields such as synchronized rise of guide way climbing frame (GWCF), formation control of mobile robots, distributed coordination of multiple dynamic systems (also known as multi-agent systems [1][2][3][4][5][6]), has achieved rapid development in recent decades. Consensus is one of the most popular topics in this area, which has received significant attention from numerous researchers [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the real and imaginary parts of the eigenvalues of the Laplacian matrix have great effect on achieving consensus . Over the past decade, the leader‐following consensus problem has been studied widely by researchers . The motions of followers are influenced by the leader where the motions of the leader is independent.…”
Section: Introductionmentioning
confidence: 99%